Implementasi Inovasi Digital pada Rabita.id dalam Meningkatkan Produksi dan Pemasaran Produk Tas Sasirangan - Hartini, Sri; Dewi Dewantara; Nuruddin Wiranda; Norzahidah, Selvia Dina; Hawalida Rizki (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
The problems faced by Community Service (PkM) program partners, namely Small and Medium Enterprises (UMKM) Rabita tas Sasirangan, are production and marketing problems. Therefore, the Community Service team carried out activities aimed at increasing production capacity and increasing the attractiveness of Rabita tas Sasirangan with a marketing strategy through digital innovation. The activity methods include socialization, training, application of technology, mentoring and evaluation, and program sustainability. The results of the implementation of the community service activities were carried out well. This is supported by (1) the creation and implementation of an e-inventory website, namely https://rabita.id/inventory and the setting up of computer embroidery tools to increase production capacity; (2) the creation and implementation of an e-catalog website, namely https://rabita.id to increase marketing. Through the implementation of e-inventory and embroidery tool set-up, partners find it easier to plan and evaluate production activities. Through the implementation of e-catalog partners can reduce costs, reach a wider market and this supports penetrating the export market. Through the implementation of digital innovation, production and marketing effectiveness can be increased.